Discoidin domain receptor 2 deficiency predisposes hepatic tissue to colon carcinoma metastasis. Issue 10 (9th November 2011) - Badiola, Iker; Olaso, Elvira; Crende, Olatz; Friedman, Scott L; Vidal-Vanaclocha, Fernando
Abstract : Background: The transdifferentiation of hepatic stellate cells (HSCs) into myofibroblasts is a major mechanism for stroma development in hepatic metastasis, but their regulatory pathways remain unclear. Transdifferentiated HSCs from fibrotic liver express high levels of the fibrillar collagen receptor discoidin domain receptor 2 (DDR2), but it is unclear if DDR2 plays a direct profibrogenic role in the tumour microenvironment. Aim: To assess the impact of DDR2 on the prometastatic role of HSC-derived myofibroblasts. Methods: Hepatic metastases were induced in DDR2 −/− and DDR2 +/+ mice by intrasplenic injection of MCA38 colon carcinoma cells, and their growth and features were characterised. Stromagenic, angiogenic and cancer cell proliferation responses were quantified in metastases by immunohistochemistry. The adhesion-, migration- and proliferation-stimulating activities of supernatants from primary cultured DDR2 −/− and DDR2 +/+ HSCs, incubated in MCA38 cell-conditioned medium, were evaluated in primary cultured liver sinusoidal endothelium cells (LSECs) and MCA38 cells. Gene expression signatures from freshly isolated DDR2 −/− and DDR2 +/+ HSCs were compared and DDR2-regulated genes were studied by RT-PCR under basal conditions and after stimulation with MCA38 tumour-conditioned media. Results: Metastases were increased three fold in DDR2 −/− livers, and contained a higher density of α−smooth muscle actin-expressing myofibroblasts, CD31-expressing microvessels and Ki67-expressing MCA38 cells than metastases in DDR2 +/+ livers. Media conditioned by MCA38-activated DDR2 −/− HSCs significantly increased adhesion, migration and proliferation of LSECs and MCA38 cells, compared with DDR2 +/+ HSCs. DDR2 deficiency in HSCs led to decreased gene expression of interferon γ-inducing factor interleukin (IL)-18 and insulin-like growth factor-I; and increased gene expression of prometastatic factors IL-10, transforming growth factor (TGF)β and vascular endothelial growth factor (VEGF), bone morphogenetic protein-7 and syndecan-1. MC38 tumour-conditioned media further exacerbated expression changes in DDR2-dependent IL-10, TGFβ and VEGF genes. Conclusion: DDR2 deficiency fosters the myofibroblast transdifferentiation of tumour-activated HSCs, generating a prometastatic microenvironment in the liver via HSC-derived factors. These findings underscore the role of stromal cells in conditioning the hepatic microenvironment for metastases through altered receptor–stroma interactions.